THE ROLE OF YOUTUBE-BASED LEARNING MEDIA IN ENHANCING STUDENTS' LEARNING CREATIVITY - Susandi, Susandi (Proceeding International Seminar of Islamic Studies, 2024)
Youtube-based learning media helps teachers convey information to students. Because it combines sound and images, this type of learning media has the potential to enhance students' learning creativity. Islamic Religious Education at SMP Negeri 4 Tanjung Beringin utilizes Youtube media, utilizing available videos to create materials that are easily understood by students. The level of student participation in class and their activity in participating in learning shows the success of efforts to enhance students' creativity in Islamic Religious Education through Youtube. The aim of this research is to explain how the implementation of Youtube-based learning media at SMP  Negeri  4  Tanjung  Beringin  and  its  role  in  enhancing  students'  learning  creativity.  The research method used is descriptive qualitative, with data collection through interviews and observations. The results show that students have used this Youtube media in Islamic Religious Education to understand lesson materials, and Youtube as a learning media can enhance students' learning creativity.